2008
DOI: 10.1186/1744-9081-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early onset otitis media on brainstem and cortical auditory processing

Abstract: Background: Otitis media (OM) leads to significant reduction in the hearing sensitivity. The reduced auditory input, if in the early years of life when the auditory neural system is still maturing, may adversely influence the structural as well as functional development of the system. Past research has reported abnormalities in both the structure and function of brainstem nuclei following auditory deprivation, but, it has not necessarily focused on children who had OM in their first year of life. It can also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 24 publications
6
35
0
13
Order By: Relevance
“…The results of SG relative to lower performance in temporal tests shown here are supported by electrophysiological studies of the auditory pathway, both in early (7) and in late potentials (13) . The delay of absolute latency of wave V, as well as greater I-V interpeak value in the brainstem auditory evoked potential at the age of 8 was positively associated with a higher frequency of OME episodes in the first years of life (7) .…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The results of SG relative to lower performance in temporal tests shown here are supported by electrophysiological studies of the auditory pathway, both in early (7) and in late potentials (13) . The delay of absolute latency of wave V, as well as greater I-V interpeak value in the brainstem auditory evoked potential at the age of 8 was positively associated with a higher frequency of OME episodes in the first years of life (7) .…”
Section: Discussionsupporting
confidence: 78%
“…The delay of absolute latency of wave V, as well as greater I-V interpeak value in the brainstem auditory evoked potential at the age of 8 was positively associated with a higher frequency of OME episodes in the first years of life (7) . The prolongation of I-V and I-III interpeak latencies were also related to ROME in early life in children aged 3, but not those aged 4 and 5 years (13) . In fact, the changes found in the brainstem auditory evoked potential may be justified, as experimental studies identified structural changes in the cochlear nuclei, medial olivary complex, and inferior colliculus, that is, from the low trunk to the high trunk (18) .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, significant hearing loss is also associated with recurrent otitis media (26). Thus, the present study aimed at investigating the audiological characteristics of a known case of Kartagner's syndrome with special emphasis on auditory processing disorders.…”
Section: Discussionmentioning
confidence: 99%